Characterisation of diphtheria monoclonal antibodies as a first step towards the development of an in vitro vaccine potency immunoassay. (January 2021) - Riches-Duit, Rebecca; Hassall, Laura; Kogelman, Amy; Westdijk, Janny; Dobly, Alexandre; Francotte, Antoine; Stickings, Paul
Abstract: Immunoassays are used for routine potency assessment of several vaccines, in some cases having been specifically developed as alternatives to in vivo potency tests. These methods require at least one well characterised monoclonal antibody (mAb) that is specific for the target antigen. In this paper we report the results of the comprehensive characterisation of a panel of mAbs against diphtheria with a view to select antibodies that can be used for development of an in vitro potency immunoassay for diphtheria vaccines. We have assessed binding of the antibodies to native antigen (toxin), detoxified antigen (toxoid), adsorbed antigen and heat-altered antigen. Antibody function was determined by a cell-based toxin neutralisation test and diphtheria toxin-domain recognition was determined by Western blotting. In addition, antibody affinity was measured, and epitope competition analysis was performed to identify pairs of antibodies that could be deployed in a sandwich immunoassay format. Not all characterisation tests provided evidence of "superiority" of one mAb over another, but together the results from all characterisation studies allowed for selection of an antibody pair to be taken forward to assay development.